Keetsahnak: our missing and murdered Indigenous sisters - Anderson, Kim; Campbell, Maria; Belcourt, Christi (The University of Alberta Press, 2018)
«In Keetsahnak / Our Murdered and Missing Indigenous Sisters, the tension between personal, political, and public action is brought home starkly. This important collective volume both witnesses the significance of the travelling exhibition Walking With Our Sisters and creates a model for antiviolence work from an Indigenous perspective. The contributors look at the roots of violence and how it diminishes life for all. They acknowledge the destruction wrought by colonial violence, and also look at controversial topics such as lateral violence, challenges in working with "tradition," and problematic notions involved in "helping." Through stories of resilience, resistance, and activism, the editors give voice to powerful personal testimony and allow for the creation of knowledge.»– Provided by publisher.
Le texte de Knott, Helen (2018) Violence and Extraction: Stories from the Oil Fields, a été donné en lecture au cours POL4105.
Keywords: activisme; amériques; anti-violence; approches et analyses; canada; cours; droits des femmes*; droits des femmes* autochtones; féminicide; féminisme autochtone; histoire et politique; intersectionnalité; militance; pol4105; premier cycle; régions géographiques; résistance; système colonial; systèmes d'oppressions; thématiques; violences